Особенности художественной речи В. М. Гаршина (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article analyses the peculiarities of artistic speech of a famous Russian writer V. M. Garshin and defines the role of expressive means in his fiction.